A Chebyshev Spectral Method with Null Space Approach for Boundary-Value Problems of Euler-Bernoulli Beam - C. P. Hsu; C. F. Hung; J. Y. Liao (Shock and Vibration)
We proposed a Chebyshev spectral method with a null space approach for investigating the boundary-value problem of a nonprismatic Euler-Bernoulli beam with generalized boundary or interface conditions. It is shown here that, with few vital improvements, a Chebyshev spectral collocation approach can be systematically applied to modeling nonprismatic Euler-Bernoulli beams with eigenvalue embedded tip-massed boundary conditions as well as the jump conditions that appear at the stepped interfaces. This study also presents a numerical stable asymptotic modal solution for the higher-order modes of a partially clamped beam and show that the proposed approach validates the robust higher-order modal solutions. Through a sequence of four increasingly complicated examples, using the proposed approach with higher-order modes, generalized boundary conditions, and interface jump conditions of nonprismatic beams, the results are in excellent agreement with those reported in the literature using various other approaches.